NH3 Oxidation Mechanism over Cu/SAPO‐34 Catalysts Prepared by Different Methods. Issue 7 (18th May 2014) - Yu, Tie; Wang, Jun; Huang, Yu; Shen, Meiqing; Li, Wei; Wang, Jianqiang
Abstract NH3 oxidation mechanism and its inhibition effect on the selective catalytic reduction of NOx by NH3 (NH3–SCR) reaction over two series of Cu/SAPO‐34 catalysts were studied. It was found that the different NO conversions were induced by the diverse NH3 oxidation degree. X‐ray diffraction, scanning electron microscopy, H2 temperature‐programmed reduction (H2–TPR), and CO diffuse reflectance infrared Fourier transform spectroscopy (CO–DRIFTS) analyses were conducted to estimate the Cu species distribution. The TPR results showed that the CuO species was dominant in impregnated Cu/SAPO‐34 samples, and the ion‐exchanged Cu/SAPO‐34 samples contained more isolated Cu2+ species. Furthermore, H2–TPR, electron paramagnetic resonance, and CO–DRIFTS analyses were utilized to quantify the CuO, Cu2+, and Cu+ species. The results together with the kinetic results revealed the CuO is the active site for NH3 oxidation, and the NH3 oxidation over Cu/SAPO‐34 sample consists two steps: (a) NO production; (b) further NO consumption by adsorbed NH3 species on Cu2+ sites. Finally, the inhibition of NH3 oxidation on NH3–SCR activity was explained and the NO conversion at high temperature was related to the Cu2+/CuO ratio in Cu/SAPO‐34 sample.